Effects of steel fibers and concrete strength on flexural toughness of ultra-high performance concrete with coarse aggregate - Shangwei Wang; Haitang Zhu; Fan Liu; Shengzhao Cheng; Bo Wang; Lin Yang (Case Studies in Construction Materials, 2022)
In order to investigate the influence of steel fiber content and concrete strength on the flexural toughness of ultra-high performance concrete with coarse aggregate (CA-UHPC), unnotched and notched beams were prepared for flexural tests. Three groups with water-binder ratios of 0.15，0.17, 0.19 were investigated, and the fiber contents of each group were 1.5%, 2.0%, 2.5%, and 3.0%, respectively. The JG/T-472–2015 and CECS13 methods were used to evaluate the test results. The results showed that when the fiber content is from 1.5% to 2%, the toughness efficiency is the highest. Pearson correlation coefficients was an effect way to evaluate the relationships between compressive strength and equivalent flexural strength, peak load and peak deflection of specimens. The fracture energy of the specimens increased linearly with the steel fiber contents. With the increasing of flexural strength, the fracture energy showed a trend of increase before decrease，and the fracture energy was the largest when the flexural strength was 24.1 MPa. Furthermore, according to the experimental fact, a new approach was proposed to modify the CECS13 method. By comparison, the modified method has better predictive validity.